Analysis of E-Service Quality Attributes in Delivery Service Application Using the Kano Model - Kumala, Khofifah Ela; Haunan Damar; Imam Nuryanto; Handy Nur Cahya (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
GoSend as an instant delivery service from Gojek plays an important role in meeting the demand for fast and reliable delivery. However, there are still challenges in terms of service quality, customer satisfaction, and competitiveness in the digital logistics industry. This study analyzes GoSend's electronic service quality attributes using the Kano Model to identify the factors that most influence customer satisfaction. The quantitative method is applied through a survey of 206 GoSend users in Semarang, with the integration of E-Servqual indicators and Kano Model attributes. The results of the study show that most service attributes fall into the